439 TRANSIENT SEVERE MITRAL REGURGITATION IN REVERSED TAKOTSUBO SYNDROME. (15th December 2022) - Leopizzi, Alessandra; Santoro, Francesco; Costantino, Roberto; Giorda, Gianpaolo; Passero, Tommaso; Ignone, Gianfranco; Brunetti, Natale Daniele
Abstract: A 65-years old Caucasian woman was referred to the emergency department for chest pain, dyspnoea and high systolic blood pressure. In the previous days she complained a constant state of anxiety and worries due to family troubles. At the admission 12 – lead EKG showed sinus rhythm, ST-T segment depression >1 mm in the lateral and anterior leads (from V2 to V6). Laboratory exams showed elevated values of high sensivity troponin levels (high-sensitive troponin: 41 pg/mL – maximum laboratory cut off value: 12 pg/mL). Bedside echocardiogram showed an LVEF of 40% due to apical hyperkinesis, akynesis of the basal segments and hypokinesis of the mid segments of the left ventricle; a severe double jet MR (Fig.1); a type II diastolic dysfunction (E/A: 1, 5; E/e': 14). Several B lines (> 3) were present in all pulmonary regions assessed by lung POCUS. Cardiac angiography demonstrated non obstructive coronary artery disease. Left ventriculography showed an hyperdynamic apex and severe basal hypokinesis. Clinical and functional status rapidly improved. Daily EKGs were registered with a progressive resolution of the ST-T segment depression. She was discharged on the 7th days and the TTE in pre-discharge showed an LVEF of 60%, without wall motion abnormalities and complete recovery of mitral regurgitation. We report a case of reversible severe mitral regurgitation in a patient with basal ballooning TTS. Mital regurgitation is generally described in the contest of classical apical TTS. The potential mechanisms for severe MR are similar to those of acute myocardial infarction. Admission and daily echocardiographic evaluation is crucial in this subset of patients, with a tailored therapy following the severity of mitral valve disease. Fig. 1